3D LiMn2O4 Thin Film Deposited by ALD: A Road toward High‐Capacity Electrode for 3D Li‐Ion Microbatteries. Issue 14 (17th February 2022) - Hallot, Maxime; Nikitin, Viktor; Lebedev, Oleg I.; Retoux, Richard; Troadec, David; De Andrade, Vincent; Roussel, Pascal; Lethien, Christophe
Abstract: Miniaturized electronics suffer from a lack of energy autonomy. In that context, the fabrication of lithium‐ion solid‐state microbatteries with high performance is mandatory for powering the next generation of portable electronic devices. Here, the fabrication of a thin film positive electrode for 3D Li‐ion microbatteries made by the atomic layer deposition (ALD) method and in situ lithiation step is demonstrated. The 3D electrodes based on spinel LiMn2 O4 films operate at high working potential (4.1 V vs Li/Li + ) and are capable of delivering a remarkable surface capacity (≈180 μAh cm −2 ) at low C‐rate while maintaining more than 40 μAh cm −2 at C/2 (time constant = 2 h). Both the thickness of the electrode material and the 3D gain of the template are carefully tuned to maximize the electrode performance. Advanced characterization techniques such as transmission electron and X‐ray transmission microscopies are proposed as perfect tools to study the conformality of the deposited films and the interfaces between each layer: no interdiffusion or segregation are observed. This work represents a major issue towards the fabrication of 3D‐lithiated electrode by ALD—without any prelithiation step by electrochemical technique—making it an attractive solution for the fabrication of 3D Li‐ion solid‐state microbatteries with semiconductor processing methods. Abstract : The fabrication of a LiMn2 O4 thin film electrode for 3D Li‐ion microbatteries is demonstrated by the atomic layer deposition method and in situ lithiation step. Four layers (Al2 O3 /Pt/LiMn2 O4 /Li3 PO4 ) are successively deposited on 3D silicon scaffold. The 3D electrode delivers approximately 180 μAh cm −2 at low C‐rate while maintaining more than 40 μAh cm −2 at C/2.